Automatisasi Pompa Irigasi pada Sistem Irigasi Tetes Berbasis Mikrokontroller Arduino Uno - Hasanah, Huswatun Ida Lailatun (Lembaga Yasin AlSys, 2022)
This drip irrigation system is a special water supply system in the root area.so that when carrying out irrigation activities, you can use water with a small discharge because it is only needed in the root area, in addition, technology greatly facilitates humans in various fields, one of which is agriculture. Therefore, with the internet of things (IOT) method, the drip irrigation system can be modified into automatic drip irrigation where the importance of this automatic drip irrigation system is in agriculture for sustainable agriculture in areas with limited water sources.The research method is experimental with a microcontroller as a control system, a relay as an LCD automatic switch as an output system and a sensor as a soil moisture reader. the results showed significant results where experiment 1, experiment 2, experiment 3, experiment 4, experiment 5 soil moisture sensor at 10-90% water percentage the pump status was on and off at 100% water percentage or soil saturated with water conditions.